Penyisipan Kode Dalam Sinyal Iklan Radio Siaran Niaga Sebagai Penanda Identitas Kepemilikan - Wahyu Dewanto; M. Farid Susanto; Sujoko Sumaryono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2012)
Advertisements broadcasting service on radio is required to report data after performing broadcast correctly and should be accountable to the owners of ads on the date, hours of broadcasting and the number of ads that aired under the contract. Therefore, it is necessary to monitor the ads in accordance with the contract between the ads owner and the radio broadcaster. The monitoring can be done by code marking inside the ads as the identity of the owner. The insertion of the Custom DTMF code through the mixing signal was done using the principle of steganography in the time domain. This research was conducted with a variety of ads audio signal that mixed with noise signal and then analyzed regarding on the placement of the custom DTMF code. For detecting on the receiver side, the DTMF Custom signal must have the magnitude level properly. The results showed that the ads audio signal and the inserted custom DTMF codes can be read well by the detector and it wasn’t interfere the ads signal heard by the audience.